Analysis of Antidiabetic Drug Utilization at Cilacap Regional General Hospital in 2022 Using ATC/DDD and DU90% Methods - Irma Nur Oktavina; Sunarti; Galih Samodra (Viva Medika, 2024)
Diabetes mellitus is a chronic disease caused by metabolic disorders characterized by elevated blood glucose levels or hyperglycemia. The aim of diabetes mellitus treatment is to control blood glucose levels within the normal range, eliminate accompanying clinical symptoms, and reduce the risk of acute complications. To achieve therapeutic goals, pharmacological therapy can be administered using antidiabetic drugs. This research is an observational study involving retrospective data collection of outpatients with type 2 diabetes mellitus who used antidiabetic drugs. The prescribed antidiabetic drugs were then analyzed using the Anatomical Therapeutic Chemical (ATC) and Defined Daily Dose (DDD) methods. Data on antidiabetic drugs were collected and entered into the Microsoft Excel program to calculate the DDD/1000 KPRJ value and the 90% Du segment. The results showed that there were 7 antidiabetic drugs used, namely glimepiride, gliquidone, gliclazide, metformin, acarbose, vildagliptin, and pioglitazone, with glimepiride having the highest DDD value of 445.92 DDD/1000 KPRJ and gliquidone having the lowest DDD value of 128.70 DDD/1000 KPRJ. Meanwhile, glimepiride and metformin were the antidiabetic drugs included in the 90% Du segment.